Snapshot imprinting as a tool for surface mapping and identification of novel biomarkers of senescent cells. Issue 24 (11th November 2022) - Piletska, Elena; Thompson, Dana; Jones, Rebecca; Cruz, Alvaro Garcia; Poblocka, Marta; Canfarotta, Francesco; Norman, Rachel; Macip, Salvador; Jones, Donald J. L.; Piletsky, Sergey
Abstract : An effective snapshot imprinting procedure was developed for analysis of proteins expressed by a cell or tissue. As an example, the proteins differentially expressed by senescent cells were identified and compared with standard proteomics technique. Abstract : Cellular senescence has proved to be a strong contributor to ageing and age-related diseases, such as cancer and atherosclerosis. Therefore, the protein content of senescent cells is highly relevant to drug discovery, diagnostics and therapeutic applications. However, current technologies for the analysis of proteins are based on a combination of separation techniques and mass spectrometry, which require handling large sample sizes and a large volume of data and are time-consuming. This limits their application in personalised medicine. An easy, quick and inexpensive procedure is needed for qualitative and quantitative analysis of proteins expressed by a cell or tissue. Here, we describe the use of the "snapshot imprinting" approach for the identification of proteins differentially expressed by senescent cells. Molecularly imprinted polymer nanoparticles (MIPs) were formed in the presence of whole cells. Following trypsinolysis, protein epitopes protected by complex with MIPs were eluted from the nanoparticles and analysed by LC-MS/MS. In this work, "snapshot imprinting" was performed parallel to a standard proteomic "shaving approach", showing similar results. The analysis by "snapshot imprinting" identified three senescent-specific proteins: cell division cycle 7-related protein kinase, partitioning defective three homolog B and putative ATP-dependent RNA helicase DHX57, the abundance of which could potentially make them specific markers of senescence. Identifying biomarkers for the future elimination of senescent cells grants the potential for developing therapeutics for age-related diseases.